Cyber security based on mean field game model of the defender: Attacker strategies - Li Miao; Shuai Li (International Journal of Distributed Sensor Networks, 2017)
The transmission process of information among computers of network is considered as the procedure of interactive behaviors. In this article, we present a mean field game model for the binary interactive behaviors between the malicious attackers and the defenders. We first discuss the evolution of the states of the malicious attackers and the defenders using the susceptiable-infective-Removal epidemic model in which we take into account the stochastic process of the propagation of the infected computers and the attack intensity. Then, we formulate the mean field game consistency stability problem generated by a Hamilton–Jacobi–Bellman equation of the individual player and the fixed-point problem. Finally, we derive the optimal individual strategy with an appropriate assumption that the response time of the defense system is faster than the infection rate.